LA SATIRE SOCIOPOLITIQUE DANS L’ESTHETIQUE ROMANESQUE DE CHARLES DJUNGU SIMBA - Jacques MUKONKOLE Lukombe, (IJRDO - Journal of Social Science and Humanities Research, 2022)
This article attempts to prove that Cite 15 and We Failed are satirical works. They denounce the flaws that are eating away at African countries, in general and those of Central Africa, in particular. Indeed, Charles DJUNGU Simba demonstrates through these works, the socio-political realities of these countries; which contrast with the economic potential and human resources that most African countries abound. Their leaders behave like dictators. They proceed by strong methods to keep their people in terror, and squander public funds. As a result, countries are dying. Basic socio-economic infrastructure is lacking, arbitrary arrests are commonplace, the people live in the most glaring misery, etc.In order to get out of the rut, Charles DJUNGU Simba proposes the change of mentality. Rather than sink into defeatism, African peoples must show self-empowerment, a sense of responsibility and a spirit of creativity.